Identifikasi Waste Tahap Pra Analitik dengan Pendekatan Lean Hospital di Laboratorium Patologi Klinik RS XYZ Depok Jawa Barat Tahun 2021 - Rini Prasetyo Wahyu Wijayati; Dumilah Ayuningtyas (Jurnal Manajemen Kesehatan Indonesia, 2021)
ABSTRACT               The pre-analytic stage includes a series of processes that are difficult to define because they occur in different places and times. Pre-analytical stage errors account for 50% to 70% laboratory error. The research aims to identify waste and provide recommendations for improvement. This type of research is operational research with a mix method research design. Quantitative data from direct observation of the laboratory examination process. Qualitative data from in-depth interviews with Laboratory Medical Technical Analysts (ATLM), on duty doctors and nurses. Non-participant observations use themethod Time and Motion study and calculate the time of each pre-analytical stage activity using a stopwatch to get the standard movement of the sample staged effectively and efficiently. Analysis with lean stages identify activities that do not provide added value (non added value) and waste (waste). Exploring the root causes of problems through in-depth interviews using the 5 (five) Whys approach and proposing recommendations for improvement. The results of the average length of time for the pre-analytic stage are due to the waiting time for new samples due to hemolysis samples. Waste found waiting for samples to be sent back (waiting time), no inspection orders, non-standard identity stickers (defect) and sticker repair (over processing). Phlebotomy training, re-education on handling laboratory specimens for nurses as well as SOPs on laboratory examination packages and sample handover, are expected to reduce pre-analytic waste.Keywords: Waste, Pre Analytical Stage, Concept  Lean ABSTRAKTahap pra analitik mencakup serangkaian proses yang sulit didefinisikan karena terjadi  ditempat  dan waktu yang berbeda. Kesalahan tahap pra analitik menyumbang kesalahan hasil laboratorium sebesar 50% hingga 70%. Penelitian bertujuan mengidentifikasi pemborosan  dan  memberikan rekomendasi perbaikan. Jenis penelitian adalah penelitian operasional dengan disain penelitian mix method. Data kuantitatf  dari observasi langsung proses pemeriksaan laboratorium. Data kualitatif  dari  wawancara mendalam dengan Analis Teknis Medik Laboratorium (ATLM), dokter jaga dan perawat. Observasi non partisipan menggunakan metode Time and Motion study serta  menghitung waktu setiap kegiatan tahap pra analiitk  menggunakan stopwatch untuk mendapatkan pergerakan standar sampel ditahap secara efektif dan efisien. Analisis dengan tahapan lean mengidentifikasi kegiatan  yang tidak memberikan nilai tambah ( non added value) dan  pemborosan (waste). Menggali akar penyebab masalah melalui wawancara mendalam menggunakan pendekatan 5 (lima)  Whys dan mengusulkan  rekomendasi perbaikan. Hasil rata rata lama waktu tahap pra analitik disebabkan waktu tunggu sampel baru karena sampel hemolisis. Waste yang ditemukan menunggu sampel dikirim ulang (waiting time), tidak ada order pemeriksaan, stiker identitas tidak standar (defect) dan perbaikan stiker (over processing). Pelatihan plebotomi, re edukasi penanganan spesimen laboratorium untuk perawat serta SPO tentang paket pemeriksaan laboratorium dan serah terima sampel, diharapkan dapat mengurangi pemborosan tahap pra analitik.